2004
DOI: 10.1111/j.1464-410x.2004.04908.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in prostate disease symptoms and visits to the general practitioner among three ethnic groups in New Zealand

Abstract: Symptom Score and yearly GP attendance questions were completed by 862 subjects with no history of prostate cancer. RESULTSThere were no significant differences in LUTS among the ethnic groups ( P = 0.80) but symptom scores were positively correlated with age only for NZ Europeans ( P < 0.001, r = 0.179). Overall, NZ populations have a lower prevalence of LUTS than is evident for ethnic groups in other countries. Pacific Islanders attended the GP more often than both NZ Europeans and Maori. CONCLUSIONEthnic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…That being mentioned, majority of the participants and target participants have QoL of 1 and 2 (47.1% and 50% respectively), which depicts that the consult were not due to symptomatic consult, but rather due to prostate health awareness. The mean age 60.4±9.85 among the recruited participants in the PaDRE ka Day was consistent with average age of participants reported from the other existing regional and international prostate health awareness program; likewise, it was consistent with the description of international LUTS and prostate cancer epidemiology [713]. …”
Section: Discussionsupporting
confidence: 83%
“…That being mentioned, majority of the participants and target participants have QoL of 1 and 2 (47.1% and 50% respectively), which depicts that the consult were not due to symptomatic consult, but rather due to prostate health awareness. The mean age 60.4±9.85 among the recruited participants in the PaDRE ka Day was consistent with average age of participants reported from the other existing regional and international prostate health awareness program; likewise, it was consistent with the description of international LUTS and prostate cancer epidemiology [713]. …”
Section: Discussionsupporting
confidence: 83%
“…Population‐based studies suggest international variations in the incidence of LUTS, even between countries of similar ethnicity [6], with prevalence values of 18–59%[7]. Witjes et al [8] found that not all symptoms were affected equally, with only 10 of 20 assessed showing international variations.…”
Section: Discussionmentioning
confidence: 99%